Comparison of three respiratory physical therapy techniques and their impact on pulmonary function restoration among cardiac surgery patients in hospital settings - V. V. Vitomskyi (Zaporožskij Medicinskij Žurnal)
The aim. To compare three respiratory physical therapy techniques and their impact on pulmonary function restoration among cardiac surgery patients in hospital settings.